2001
DOI: 10.2118/69742-pa
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Modeling of the SAGD Process - Enhancing SAGD Performance with Periodic Stimulation of the Horizontal Producer

Abstract: Summary Experiments on initial stages of the steam-assisted gravity drainage (SAGD) process were carried out, using two-dimensional (2D) scaled reservoir models, to investigate production process and performance. Expansion of the initial steam chamber, its shape and area, and its temperature distributions were visualized with video and thermal-video pictures. The relationship between isotherms and steam-chamber interface was investigated to study the drainage mechanism. Temperature at the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 5 publications
2
49
0
Order By: Relevance
“…As evident through some previous experimental studies on this phenomenon [3,6,[8][9][10][11], it has been suggested that W/O emulsions are mostly produced during the SAGD process. Especially, Sasaki et al [8,9] conducted experimental studies of SAGD process by using two-dimensional scaled reservoir model to investigate fluids flow characteristics in the steam chamber. Furthermore, they also carried out visualization of micro-phenomena at inclined interface on the side of steam chamber by means of a high-resolution optical-fiber scope [3].…”
Section: Introduction mentioning
confidence: 84%
“…As evident through some previous experimental studies on this phenomenon [3,6,[8][9][10][11], it has been suggested that W/O emulsions are mostly produced during the SAGD process. Especially, Sasaki et al [8,9] conducted experimental studies of SAGD process by using two-dimensional scaled reservoir model to investigate fluids flow characteristics in the steam chamber. Furthermore, they also carried out visualization of micro-phenomena at inclined interface on the side of steam chamber by means of a high-resolution optical-fiber scope [3].…”
Section: Introduction mentioning
confidence: 84%
“…A calculation of the heat balance of the system shows that the net heat, which is transferred from the injected hot water generated by the surplus heat, is sufficient for MH dissociation. In the hot-water injection method, dual horizontal wells are used, similar to the steam assisted gravity drainage (SAGD) method for oil sands (Sasaki et al,2001) [20] to carry the injected hot water and the produced gas and water. Following the SAGD method, two wells drilled 5m apart at upper region 2m from its boundary of the MH reservoir are used to create the depressurizing area around the wells at the initial stage, connecting the two wells as shown in Fig.7.…”
Section: Hot-water Injection Methods Using Dual Horizontal Wellsmentioning
confidence: 99%
“…The topic of "emulsification phenomenon" during the typical SAGD process was covered in the literature based on the experiments conducted using scaled physical models as well as field-scale data [24,[26][27][28][29][30][31]. According to the field-scale trials of the SAGD process, the produced liquid is in the emulsion state composed of mobilized oil and water (either stable or unstable depending on the physicochemical characteristics of the interacting liquids as well as process operating conditions).…”
Section: Emulsification Phenomenonmentioning
confidence: 99%